2018
DOI: 10.1149/2.0321802jes
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Liquid Structure and Ion Formation in Magnesium Borohydride Electrolyte Using Density Functional Theory

Abstract: Rechargeable magnesium batteries have attracted much interest due their high volumetric capacity, potential for safe operation, and the natural abundance of magnesium. However, the development of magnesium batteries for practical applications has been obstructed by the lack of understanding of the liquid structure of electrolytes. Herein, we use quantum density functional theory coupled with a continuum solvation model to investigate the structure of Mg(BH 4 ) 2 in two ethereal solvents: tetrahydrofuran (THF),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 55 publications
6
21
0
Order By: Relevance
“…These attributes are contrasted with those of Mg(BH4)2 electrolytes, which have been the subject of several recent studies. 5,[18][19][20][21] Our integrated investigation demonstrates that the relative concentration of ionic clusters is enhanced in high concentration Ca(BH4)2/THF, and that BH4is strongly coordinated to Ca 2+ within these clusters. From this analysis, we propose that the electroactive cationic species is CaBH 4 + and that this species is responsible for delivery of Ca 2+ to the electrode.…”
Section: Introductionmentioning
confidence: 75%
“…These attributes are contrasted with those of Mg(BH4)2 electrolytes, which have been the subject of several recent studies. 5,[18][19][20][21] Our integrated investigation demonstrates that the relative concentration of ionic clusters is enhanced in high concentration Ca(BH4)2/THF, and that BH4is strongly coordinated to Ca 2+ within these clusters. From this analysis, we propose that the electroactive cationic species is CaBH 4 + and that this species is responsible for delivery of Ca 2+ to the electrode.…”
Section: Introductionmentioning
confidence: 75%
“…Focusing on BH 4 − ‐containing electrolytes, both experimental studies [15,50] and calculations [61,62] for several electrolytes have concluded that the dissociation of the Mg 2+ −BH 4 − coordination is a key aspect for Mg deposition, which, in ether‐type solvents, is influenced by the number of coordinating oxygen atoms or possibly also by coordinating TFSI − ions. The Mg 2+ coordination in BH 4 − ‐ and TFSI − ‐containing diglyme was investigated by Hu et al .…”
Section: Resultsmentioning
confidence: 99%
“…À -containing electrolytes, both experimental studies [15,50] and calculations [61,62] for several electrolytes have concluded that the dissociation of the Mg 2 + À BH 4…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…The In addition, computations were used to understand the role of coordination and effects of the solvent on the solubility and dissociation in these electrolytes. [80][81] Significant and irreversible salt agglomeration in all glymes ranging from THF to tetraglyme was found in all non-dilute borohydride salt solutions. 80 The agglomeration rate and diffusivity of Mg 2+ in longer chain ethers such as tetraglyme were at their lowest and tracked with the solvent's self-diffusivity.…”
Section: Liquid Borohydride Electrolytesmentioning
confidence: 97%